Embracing gen-z’s learning styles with a mobile enthalpy game application (MEGA) for thermochemical equation - Choo, Sze Yee; Taha, Hafsah (Jurnal Cakrawala Pendidikan, 2023)
Gen-Z is digital natives with unique learning styles. Gen Z is attracted to mobile technology and interactive visual learning materials. Therefore, the mobile game application seems to engage Gen Z in learning abstract chemistry topics. This paper focuses on the effectiveness of an Android game app, mobile enthalpy game application (MEGA) to facilitate students to write thermochemical equations and study its effect on their achievement in the topic. The study involved 72 Malaysian science matriculation students which were divided into control and treatment groups. The impact of MEGA (treatment group) versus PowerPoint slides (control group) on students’ performance in writing thermochemical equations was compared. Results showed significant differences in pre and post-test scores for students in MEGA and PowerPoint groups. Students in the treatment group surpassed the control group’s performance in the post-test scores. To conclude, the mobile game apps (MEGA) seemed to be able to promote gen Z’s achievement and interest in learning.